Determinan Partisipasi Ibu Membawa Balita ke Posyandu di Wilayah Kerja Puskesmas Sakti kecamatan Sakti Kabupaten Pidie - Ainul Mahfud; Mappeaty Nyorong; Razia Begum Suroyo; Nur Aini; Indah Anggraini (Lembaga Pengembangan Kinerja Dosen, 2024)
Posyandu is a basic health activity organized by, by and for the community assisted by health workers in a Puskesmas work area. The aim of this research was to determine the determinants of mothers' participation in bringing toddlers to posyandu in the Sakti Community Health Center Working Area, Sakti District, Pidie Regency. The research design uses a mixed method with an explanatory approach. Quantitative designs use cross sectional, qualitative designs use a narrative approach. The population in this study was 459 mothers who had toddlers aged 12-59 months in the Sakti Community Health Center Working Area, Sakti District, Pidie Regency, with a quantitative sample of 82 mothers, for the qualitative sample 3 mothers who had toddlers, 1 midwife, 1 religious figure/ or ustad. Quantitative data analysis uses univariate, bivariate and multivariate analysis, qualitative analysis uses familiarization analysis, Identifying athematic framework, indexing, charting, imapping and interpretation. The results of this study show that there is an influence on the variables of the role of health workers (p=0.025), religion (p=0.000), infrastructure (p=0.000), culture (p=0.002), AEFI (p=0.004). Multivariate research results show that there is an influence of religion (p=0.002), culture (0.011), AEFI (0.005). The results of mixed method research show that the most influential factor is religion. The conclusion of this research is that there is no determining influence on the role of health workers, infrastructure, and there is an influence of religion, culture, KIPI on the participation of mothers in bringing toddlers to posyandu in the Sakti Community Health Center Working Area, Sakti District, Pidie Regency. It is recommended to the sub-district head of Pidie sub-district to send an outstanding midwife to school in each village in order to meet the needs of midwives who live in the village..